PERUBAHAN KEBIJAKAN JABATAN PENGAJAR DI GMIT: DARI JABATAN PENUH WAKTU, KE JABATAN PERIODIK - Daud Saleh Luji; Sem Saetban (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
The Evangelical Christian Church in Timor (GMIT) has had a policy regarding full-time teaching positions since 1999. However, in 2010 a new policy was born on teaching positions that are periodically elected. The purpose of this research is to find out 1). The rationale behind the GMIT Synod's decision on the periodically elected church teaching position. 2). The relevance of teaching positions at GMIT and Calvin's views on teaching positions and teaching ministry. With a qualitative approach, the research results found regarding the rationale for the birth of the new policy are as follows: 1). Teaching positions are not only for those who have a PAK or Theology background because service positions in GMIT refer to the ecclesiology principle of institutional principles, namely the principle of priesthood and believers and ecclesia reformata semper reformanda 2). GMIT is faced with minimal financing capacity, so the absorption capacity of the little church is limited. 3). Many teaching staff with a Christian religious education background prefer to be teachers in schools (PNS), so they have not given themselves entirely to become teachers in churches, 4). The GMIT congregations are generally not financially able to finance a pastor and a teacher. According to the author, GMIT's policy regarding recruiting teaching staff who serve as teachers periodically is irrelevant to Calvin's view.